The effects of extracorporeal shock-wave therapy (ESWT) versus Mulligan concept of manual therapy in treating lateral epicondylitis = Efektywność terapii zewnątrzustrojową falą uderzeniową versus terapia manualna w koncepcji Mulligana w leczeniu zapalenia nadkłykcia bocznego - Kocjan, Janusz (Journal of Education, Health and Sport, 2016)
Kocjan Janusz. The effects of extracorporeal shock-wave therapy (ESWT) versus Mulligan concept of manual therapy in treating lateral epicondylitis = Efektywność terapii zewnątrzustrojową falą uderzeniową versus terapia manualna w koncepcji Mulligana w leczeniu zapalenia nadkłykcia bocznego. Journal of Education, Health and Sport. 2016;6(7):411-418. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58333 http://ojs.ukw.edu.pl/index.php/johs/article/view/3705 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 21.07.2016. THE EFFECTS OF EXTRACORPOREAL SHOCK-WAVE THERAPY (ESWT) VERSUS MULLIGAN CONCEPT OF MANUAL THERAPY IN TREATING LATERAL EPICONDYLITIS EFEKTYWNOŚĆ TERAPII ZEWNĄTRZUSTROJOWĄ FALĄ UDERZENIOWĄ VERSUS TERAPIA MANUALNA W KONCEPCJI MULLIGANA W LECZENIU ZAPALENIA NADKŁYKCIA BOCZNEGO Janusz Kocjan Medical University of Silesia, Doctoral Studium of School of Medicine, Katowice, Poland Śląski Uniwersytet Medyczny, Studium Doktoranckie Wydziału Lekarskiego w Katowicach SUMMARY Extracorporeal shockwave therapy (ESWT) is a conservative treatment in case of many musculoskeletal disorders, including lateral epicondylitis. The aim of the study was the assessment of the efficacy of the shockwave - compare to manual therapy treatment (Mulligan concept) in a population of consecutive patients affected by tennis elbow. 26 patients who suffered from chronic persistent tennis elbow were randomly assigned to one of the two treatment groups. Group 1 (n=13, mean age=37,14±10,07) received an extracorporeal shock wave treatment (ESWT; 2,500 shocks), while Group 2 (n=13, mean age=) was undergoing manual therapy in Mulligan concept. Visual Analogue Scale (VAS) and Patient-Rated Tennis Elbow Evaluation (PRTEE) were used. The results of the study presented here shows that ESWT and Mulligan therapy are an effective treatment of lateral epicondylitis. Both groups achieved improvement in all of analysed variables, but in case of Mulligan Concept statistical significant differences were found in 4 from 6 variables. It is concluded that ESWT and Mulligan therapy appears to be a useful non invasive treatment methods that reduces the symptoms of lateral epicondylitis. Key words: ESWT, mulligan, tennis elbow, lateral epicondylitis.